Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ 25x = x <=> 25x - x = 0 => 24x = 0 => x = 0
b/ (x - 2016) . (x - 2018) = 0
=> x - 2016 = 0 hoặc x - 2018 = 0
=> x = 2016 hoặc x = 2018
a) ( x- 55 ) . 17 = 0
x - 55 = 0 : 17
x - 55 = 0
x = 0 + 55
x = 55
Vậy x = 55
b) 25 . ( x - 75 ) = 25
x - 75 = 25 : 25
x - 75 = 1
x = 1 + 75
x = 76
Vậy x = 76
c) ( x - 5 ) ( x - 7 ) = 0
=> x - 5 = 0 hoặc x - 7 = 0
x = 0 + 5 x = 0 + 7
x = 5 x = 7
Vậy \(x\in\left\{5;7\right\}\)
d) ( x -11 ) ( x + 17 ) = 0
=> x - 11 = 0 hoặc x + 17 = 0
x = 0 + 11 x = 0 - 17
x = 11 x = -17
Vậy \(x\in\left\{11;-17\right\}\)
\(x^3-\frac{4}{25}x=0\)
\(\Rightarrow x\left(x^2-\frac{4}{25}\right)=0\)
\(\Rightarrow x=0\)hoặc \(x^2-\frac{4}{25}=0\)
Nếu \(x^2-\frac{4}{25}=0\)
\(\Rightarrow x^2=0+\frac{4}{25}\)
\(\Rightarrow x^2=\frac{4}{25}\)
=>\(x\in\left\{\frac{-2}{45};\frac{2}{45}\right\}\)
Vậy \(x\in\left\{\frac{-2}{45};\frac{2}{45};0\right\}\)
a) 85 . (x - 5) = 0
x - 5 = 0 : 85
x - 5 = 0
x = 0 + 5
x = 5
b) (x - 14) - 60 = 0
x - 14 = 0 + 60
x - 14 = 60
x = 60 + 14
x = 74
c) 75 . (x - 1) = 75
x - 1 = 75 : 75
x - 1 = 1
x = 1 + 1
x = 2
a) \(\left(x-2018\right)\cdot3=0\)
\(\Leftrightarrow x-2018=0\)
\(\Leftrightarrow x=2018\)
b) \(25\left(x-8\right)=0\)
\(\Leftrightarrow x-8=0\)
\(\Leftrightarrow x=8\)
c) \(25+\left(15+x\right)=75\)
\(\Leftrightarrow15+x=50\)
\(\Leftrightarrow x=35\)
a) -9-25=(7-x)-(25+7)
<=> −9−25=7−x−25−7
<=> -9=7-x-7
<=> -9=-x
<=> x=9
b) (x-5)(x+8)=0
<=> x-5=0 hoặc x+8=0
<=> x=5 hoặc x=-8
d) Đề sai, x đâu???
...
\(c,0< \left|x-7\right|< 3\)
\(0< x-7< 3\)
\(7< x< 10\)
\(\Rightarrow x\in\left\{8;9\right\}\)
25x .75 x = 0
( 25 x 75 ) . ( x .x ) = 0
1875 . x2 = 0
=> x = 0
Mai Thị Thanh Hoa
Ta có cách giải như sau:
25x . 75x = 0
(25 . 75) . (x .x) = 0
1875 . x . x = 0
=> x = 0